AIDMA Model Analysis on Brand Activation and Engagement Program: The Case of Mad For Makeup BT21 Edition - Saipul Bahri (Jobmark: Journal of Branding and Marketing Communication, 2023)
Mad For Makeup, a local cosmetics brand that collaborates with BT21, has adopted a Brand Activation and Engagement approach in its marketing efforts. This article analyzes the effectiveness of Mad For Makeup's efforts in implementing Brand Activation and Engagement strategies from the AIDMA Model perspective. Using a qualitative case study method, the results show that initiatives like the hashtag #MadForMakeupBT21 have achieved relatively high social media exposure, with 132.3 thousand views. In comparison, the hashtag #MadMetBT21 even reached 1.2 million views. Most participants involved in this research and connected to the AIDMA Model also support the argument that the Brand Activation and Engagement strategy implemented by Mad For Makeup BT21 Edition can be successful. This research provides valuable insight into how local cosmetics brands can leverage social media and implement effective marketing strategies to stay competitive in the cosmetics industry. Mad For Makeup's success is an example of how local brands can face competition from international brands in the ever-growing Indonesian cosmetics market.